The impact of the culture of volunteer work on the behavior of male and female students in public schools in the city of Abha - Al Majthel, Shadiah Naser (Journal of Educational and Psychological Sciences, 2023)
The study aimed to reveal the impact of the culture of volunteer work in schools on disruptive behavior among public school students in the city of Abha in the Kingdom of Saudi Arabia. To achieve the objectives of the study, the researcher used the descriptive analytical method by applying the electronic questionnaire to a random sample of (41) male and female teachers in public schools in the city of Abha. The results showed that the degree of attitudes of students in government schools towards volunteer work among government school students in the city of Abha in Saudi Arabia was very high, and the results showed that the impact and effectiveness of volunteer work on voluntary subversive behaviorAmong government school students in the city of Abha in the Kingdom of Saudi Arabia, it came at a very high degree. The results indicated that the proposals presented to support the role of volunteer work in eliminating disruptive behavior among government school students in the city of Abha in Saudi Arabia came at a very high degree. The results also showed that there was an impact with There is a statistical significance for the culture of volunteer work in government schools on disruptive behavior among government school students in the city of Abha in the Kingdom of Saudi Arabia. The study recommended the necessity of providing psychological support to students who may be vulnerable to disruptive behavior, and psychological guidance can help in understanding the reasons behind disruptive behavior and directing Students towards more positive behavior.
Keywords: volunteer work; disruptive behavior; public schools; culture of volunteer work